Pengaruh Model Guided Inquiry terhadap Hasil Belajar Siswa pada Pembelajaran Matematika Siswa SD Kota Bengkulu - Hafiza Fahmia; Victoria Karjiyati; Dalifa Dalifa (Universitas Bengkulu, 2019)
This study aims to determine the effect of guided inquiry model on student learning outcomes in Mathematics learning in grade V SD Gugus XII Kota Bengkulu. This type of research is a quasi-experimental research with the design of the study of the matching only pretest-posttest control group design. The population in this study is all students of class V SD group XII consisting of 5 elementary schools. Based on the homogeneity test results, the sample in this study were the students of grade V SDN 99 as the experimental class and the students of class V SDN 81 as the control class. The research instrument used is a matter of objective test consisting of 20 items. Data analysis used is descriptive analysis, prerequisite test and inferential analysis that is t-test. Based on data analysis of research results, obtained the average value of posttest result of experimental class using guided inquiry model that is 78,120 and control class using conventional learning that is 62,789. T-test of both sample classes with significance level? = 0.05, obtained count = 4,730 whereas ttable = 2,000, tcount> ttable so that H0 is rejected and Ha accepted. The increase of study result percentage in experiment class is higher than control class that is 83.36% in experimental class and control class 33.98%. Thus it can be concluded there is a significant effect of student learning outcomes that follow the learning using guided inquiry model.